Clinical outcomes and patient perspectives of Dental Monitoring® GoLive® with Invisalign®-a retrospective cohort study - Ismaeel Hansa; Steven J. Semaan; Nikhilesh R. Vaid (SpringerOpen, 2020)
Abstract Background The aims of the study were to compare the effects of Invisalign® with and without Dental Monitoring® (DM) GoLive® on the following parameters: treatment duration, number of appointments, number of refinements, total number of refinement aligners, and time to initial refinement. The patients' perspectives on Dental Monitoring® were also evaluated using an online questionnaire. A sample of 155 consecutively treated Invisalign® patients (67 control, 88 DM) fit the inclusion and exclusion criteria. Results The two groups were homogeneous (P > .05) for age, gender, angle classification, Little's Irregularity Index, and number of initial aligners. The DM group had significantly fewer office visits compared to the control (7.56 vs 9.82; P < .001). There were no significant differences between the DM and control groups respectively pertaining to treatment duration (14.58 vs 13.91), number of refinements (1.00 vs 0.79), number of refinement aligners (19.91 vs 19.85), and time to first refinement (9.46 vs 9.97). Questionnaire results showed that 68.8% (44 respondents) indicate that DM scans were "easy" or "very easy" to perform while 16 responders (25%) found it "difficult" or "very difficult." 71.9% (46 responders) were "satisfied or very satisfied" with the level of communication with the orthodontist using DM and 16% (10 responders) were "dissatisfied" or "very dissatisfied." The mean duration observed by patients to take a scan was 5.16 ± 3.6 min. Eighty-eight percent (56 responders) of patients prefer few office visits as possible, while 12% (8 responders) would actually prefer additional office visits. Overall, the mean satisfaction of patients with DM was 4.25 on the 5-point Likert scale. Conclusion The DM group had a significantly reduced number of appointments (7.56) compared with the control group (9.82) (a reduction of 23%) over the treatment duration. There were no significant differences between the two groups in treatment duration, number of refinements, number of refinement aligners, or time to 1st refinement. Overall, DM was well received by patients. However, there was a small percentage (usually less than 15%) that was generally unsatisfied with DM in varying aspects and preferred more frequent, traditional office visits.